Evaluation of 6 MV photon beam characteristics on Varian Clinac iX: a Monte Carlo study - Manik, Josua Timotius; Okselia, Anisza; Junios, Junios; Margaretha, Angelica; Haryanto, Freddy (International Journal of Advances in Applied Sciences, 2025)
This work aims to study the characteristics of photon beams through phase space file (PSF) analysis using Monte Carlo (MC) simulation. 6 MV photon beams from the Varian Clinac iX were simulated using PRIMO software. The beam parameters were validated by evaluating the percentage depth dose and dose profile. A full PSF was scored at the downstream end of the linear accelerator (LINAC) upper and lower parts and analyzed to determine the beam fluence profile, energy fluence profile, angular distribution, and spectral distribution. The results show that within PSF 1, the photon beam has an average scattering angle of 10.74° and a mean energy of 1.18 MeV. In PSF 2, the average scattering angle decreases to 2.63° while the mean energy increases to 1.50 MeV. The field size variation at 20×20, 30×30, and 40×40 cm2 affects both the angular and spectral distribution of the photon beam. The photon beam in PSF 2 exhibits an average scattering angle of 4.56, 6.31, and 6.66°, with corresponding mean energy values of 1.40, 1.32, and 1.30 MeV, respectively. These findings show that as the field size increases, the photon beam scatters at a larger angle while the energy decreases.